2018
DOI: 10.1186/s13006-018-0178-5
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of exclusive breastfeeding in rural South India

Abstract: BackgroundWhile breastfeeding rates have improved globally, disparities in breastfeeding practices persist particularly in rural and low resource settings. In India, only 56% of Indian mothers practice exclusive breastfeeding (EBF) for the recommended six months. As India leads the world in the number of preterm births, under 5 years of age malnutrition and neonatal mortality, understanding the factors associated with EBF can help improve the nutritional status for millions of infants. We assessed the factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 16 publications
4
44
1
3
Order By: Relevance
“…9 100 (21%) babies born were put on breast within first hour of life was reported by Vyas et al 10 In study conducted by Junaid et al, 78.28% mothers initiated breastfeeding within 6 hours of delivery whereas only 36.9% mothers initiated breast feeding within an hour was reported by Vijayalakshmi et al 11,12 The mean age of mothers in our study was 26.03±3.38 years, however in study conducted by Nishimura et al, mean age was 20.8±2.75 years. 13 Exclusive breastfeeding rate in this study was found to be 86%. However, the EBF rate as reported by Holly Nishimura et al was 48.5%.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…9 100 (21%) babies born were put on breast within first hour of life was reported by Vyas et al 10 In study conducted by Junaid et al, 78.28% mothers initiated breastfeeding within 6 hours of delivery whereas only 36.9% mothers initiated breast feeding within an hour was reported by Vijayalakshmi et al 11,12 The mean age of mothers in our study was 26.03±3.38 years, however in study conducted by Nishimura et al, mean age was 20.8±2.75 years. 13 Exclusive breastfeeding rate in this study was found to be 86%. However, the EBF rate as reported by Holly Nishimura et al was 48.5%.…”
Section: Discussionmentioning
confidence: 44%
“…However, the EBF rate as reported by Holly Nishimura et al was 48.5%. 13 Chinnasami et al reported that exclusive breastfeeding rate for six months was 72%. 14 Only 5.13% babies were exclusively breastfed till six months in study conducted by Vyas et al, Junaid et al found exclusive breastfeeding rate as 58.58% mothers.…”
Section: Discussionmentioning
confidence: 99%
“…(12) Having more antenatal care visits was associated with lower odds of delayed initiations of breastfeeding and non-exclusive breastfeeding, indicating that health promotion efforts should focus on encouraging mothers to attend these visits. (13) Furthermore, this suggests that antenatal care visits represent an effective access point for providing breastfeeding education.…”
Section: E P U B a H E A D O F P R I N Tmentioning
confidence: 99%
“…There is evidence to suggest that infants who are breastfed exclusively have 13% reduced risk of mortality compared to nonexclusively breastfed infants in low-and middle-income countries (LMICs). 15,16 In LMICs, only 37% of children are breastfed exclusively for the first 6 months of life and India is no exception. 17 According to the national family and health Survey-4, on average only 56% of Indian mothers practiced EBF (exclusive breast feeding) for the full 6 months.…”
Section: Introductionmentioning
confidence: 99%